Gender and age variation of cranial morphometric characteristics in pre-school age children - S. Y. Baibakov; N. S. Bakhareva (Сеченовский вестник, 2022)
The article discusses the morphometric neurocranium criteria for children of pre-school age (4–7) ontogenesis and evaluates the basic parameters for their possible mathematical prediction. The patients were examined by MRI. Gender variability of the neurocranium morphometric parameters in children of pre-school age (4–7) was manifested in the bigger cranium sizes in boys, with the exception of cephalic index that was bigger in girls. The study revealed moderate correlation between age and cranium longitudinal and transverse dimensions – correlation coeﬃcient was 0.41–0.74. The correlation between vertical size and the age in the period of intensive growth was rather high, the correlation coeﬃcient was 0.65–0.82. Correlation in gender and age groups was positive. The correlation allowed developing regression models and nomograms for the prediction of the cranium size, depending on the age with high informational value (95%). The size and range of their variability determined in vivo for diﬀerent age groups of postnatal ontogenesis were considered in indicators for metric data objectiﬁcation in clinical pathology diagnosing (department of magnetic resonance and computed tomography).